Young Adults with Autism Spectrum Disorder Show Early Atypical Neural Activity during Emotional Face Processing - Leung, Rachel C.; Pang, Elizabeth W.; Anagnostou, Evdokia; Taylor, Margot J. (Frontiers in Human Neuroscience, 2018)
Social cognition is impaired in Autism Spectrum Disorder (ASD). The ability to perceive and interpret affect is integral to successful social functioning and has an extended developmental course. However, the neural mechanisms underlying emotional face processing in ASD are unclear. Using magnetoencephalography, the present study explored neural activation during implicit emotional face processing in young adults with and without ASD. Twenty-six young adults with ASD and 26 healthy controls were recruited. Participants indicated the location of a scrambled pattern (target) that was presented alongside happy or angry face. Emotion-related activation sources for each emotion were estimated using the Empirical Bayes Beamformer (pcorr<0.001) in SPM12. Emotional faces elicited elevated fusiform, amygdala and anterior insula and reduced ACC activity in adults with ASD relative to controls. Within group comparisons revealed that angry versus happy faces elicited distinct neural activity in typically developing adults; there was no distinction in young adults with ASD. Our data suggest difficulties in affect processing in ASD reflect atypical recruitment of traditional emotional processing areas. These early differences may contribute to difficulties in deriving social reward to faces, ascribing salience to faces, and an immature threat processing system, which collectively could result in deficits in emotional face processing.